"Are You Having Thoughts of Suicide?" Examining Experiences With Disclosing and Denying Suicidal Ideation. Issue 10 (13th January 2017) - Hom, Melanie A.; Stanley, Ian H.; Podlogar, Matthew C.; Joiner, Thomas E.
Abstract : Objective: To characterize individuals' prior experiences with being asked whether they are having thoughts of suicide and to understand factors that affected their response accuracy. Method: Undergraduates ( N = 306) reporting a lifetime history of suicidal ideation completed a web‐based survey about their experiences being probed about suicidal thoughts. Results: Nearly two‐thirds of participants (63.1%) reported having been previously asked whether they were having thoughts of suicide, with health care providers comprising the plurality of probers. Individuals reported the greatest accuracy of ideation disclosure to mental health professionals. Stigma‐related concerns were the most common barriers to accurate disclosure of ideation, whereas wanting emotional support and the prober to understand them were cited as facilitators for accurately responding. Conclusion: A number of factors influence the accurate and inaccurate disclosure of suicidal ideation. Further research is needed to understand how to facilitate accurate disclosure of suicidal ideation across settings and populations.